Linear and Nonlinear Mendelian Randomization Analyses of the Association Between Diastolic Blood Pressure and Cardiovascular Events: The J-Curve Revisited. Issue 9 (30th November 2020) - Arvanitis, Marios; Qi, Guanghao; Bhatt, Deepak L.; Post, Wendy S.; Chatterjee, Nilanjan; Battle, Alexis; McEvoy, John W.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Recent clinical guidelines support intensive blood pressure treatment targets. However, observational data suggest that excessive diastolic blood pressure (DBP) lowering might increase the risk of myocardial infarction (MI), reflecting a J- or U-shaped relationship. Methods: We analyzed 47 407 participants from 5 cohorts (median age, 60 years). First, to corroborate previous observational analyses, we used traditional statistical methods to test the shape of association between DBP and cardiovascular disease (CVD). Second, we created polygenic risk scores of DBP and systolic blood pressure and generated linear Mendelian randomization (MR) estimates for the effect of DBP on CVD. Third, using novel nonlinear MR approaches, we evaluated for nonlinearity in the genetic relationship between DBP and CVD events. Comprehensive MR interrogation of DBP required us to also model systolic blood pressure, given that the 2 are strongly correlated. Results: Traditional observational analysis of our cohorts suggested a J-shaped association between DBP and MI. By contrast, linear MR analyses demonstrated an adverse effect of increasing DBP increments on CVD outcomes, including MI (MI hazard ratio, 1.07 per unit mm Hg increase in DBP; P <0.001). Furthermore, nonlinear MR analyses found no evidence for a J-shaped relationship; instead confirming that MI risk decreases consistently per unit decrease in DBP, even among individuals with low values of baseline DBP. Conclusions: In this analysis of the genetic effect of DBP, we found no evidence for a nonlinear J- or U-shaped relationship between DBP and adverse CVD outcomes; including MI.